THE INFLUENCE OF EXPOSURE TO GREEN ADVERTISING AND PERCEIVED RISK ON SMOOT PURCHASE INTENTION - Nisa Safitri, Aiko; Surayya Ulfa, Nurist; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
Smoot is a smart electric motorcycle brand that aims to tackle the air pollution issue in Indonesia. Smoot applies green advertising tactic on their Instagram (@smootmotor), which is targeted to Indonesians who are found to care about the environment. However, Smoot sales are still fluctuating and way under its target. It is found that there is a number of risks that is perceived by Indonesian citizens toward the usage of electric motorcycle. This study aims to find the influence of exposure to green advertising and perceived risk on Smoot purchase intention by applying Cognitive Response Approach and Theory of Planned Behavior. Using explanatory quantitative method and simple linear regression analysis technique, this study found that there is a positive significant influence of exposure to green advertising on Smoot purchase intention and there is a negative significant influence of exposure to green advertising on Smoot purchase intention